Experimental Study on Moisture Migration of Unsaturated Loess during the Freezing Process - Hui Zhang; Tiehang Wang; Enlong Liu; Mengling Hu (Advances in Civil Engineering)
To reveal the water-heat transfer mechanism of unsaturated loess, the effects of soil dry density (1.30 g/cm3, 1.50 g/cm3, and 1.65 g/cm3), moisture content (13.3%, 16.2%, and 19.4%), cold end temperature (−7°C, −10°C, and −13°C), and freezing mode on moisture migration in unsaturated loess in this paper are studied through indoor tests of moisture migration under the freezing action of large-size unsaturated loess. The results show that the temperature change in soil samples in the freezing process can be divided into three stages: rapid cooling stage, slow cooling stage, and stable stage. The higher the dry density, the closer the freezing front is to the cold end, with the initial moisture content having little effect on the freezing front, while the temperature at the cold end has a significant effect on the location of the freezing front. The total amount of moisture migration decreases with the increase of dry density, increases with the increase of moisture content, and increases with the decrease of cold end temperature. The freezing mode directly affects the distribution of moisture content and total amount of moisture migration in the frozen area.